Moving beyond genome sequencing into personalized genomic medicine: biological and computing challenges - Kristensen, David M (BioMed Central, 2011)
A report of the second annual Beyond the Genome conference held on the 19-22 September 2011 at The Universities at Shady Grove, Rockville, Maryland, USA, where increases in computing that may help make personal genomics a reality were a major focus.